Differential Induction of Apoptosis by Apple Procyanidins in TRAIL-Sensitive Human Colon Tumor Cells and Derived TRAIL-Resistant Metastatic Cells (2009)
ABSTRACT: AIM: Procyanidins (Pcy) are oligomers of catechins and epicatechins. In order to get more insight into the apoptotic effects of Pcy, we aimed to compare the death signaling pathways triggered by Pcy in TRAIL-sensitive human colon cancer cells (SW480) and in their derived TRAIL-resistant metastatic cells (SW620). METHODS: Cell death, DR4/DR5, Bcl-2/Bax proteins, mitochondrial membrane potential, and reactive oxygen species (ROS) production were analyzed by flow cytometry. Bid and cytochrome c were studied by immunoblotting and ELISA. RESULTS: Pcy (80 µg/ml) combined with exogenous TRAIL (30 ng/ml) enhanced the apoptotic effects of TRAIL in SW480 but also in SW620 cells, indicating that Pcy sensitized SW620 cells to TRAIL treatment. Pcy up-regulated the expression of death receptors DR4/DR5 of TRAIL. Activation of caspase-8 and -3 was observed in both cell lines but caspase-9 was activated only in SW620 cells. Pcy-treated SW620 cells exhibited a decrease in Bid protein level, in Bcl-2/Bax ratio, and enhanced intracellular ROS production. These events were associated with the decrease of mitochondrial membrane potential and the release of cytochrome c into the cytosol. CONCLUSION: Our data suggest that Pcy triggers apoptosis via caspase-8 and may enhance TRAIL-induced apoptosis by activation of the extrinsic pathway in both cell lines. In the TRAIL-resistant SW620 cells, the apoptotic effects of Pcy were complex and may involve a cross-talk between the extrinsic and the mitochondrial apoptotic pathways and a Pcy-triggered intracellular ROS production favoring mitochondrial disruption. These data highlight the chemopreventive potentials of apple Pcy in colorectal cancer treatments.